Immunohistochemical Protein Tracing of p15 INK4B Gene Expression in Latent Membrane Protein-1-Epetein Barr Virus Oncoprotein Infected Tissues from Ovarian Tumors Patients - Ruqaya M.J. Awadh (Journal of Global Pharma Technology, 2018)
This study was designed as a retrospective case-control study research. A total number of (150) formalin-fixed, paraffin embedded ovarian tissues was included. These tissues  were including 45 malignant ovarian tumors (which including Serous epithelial  (32 cases : 71.11%), Mucinous (9 cases :20%) and Endometrium (4 cases :8.89 %)  ,  45 benign ovarian tumors), 20 borderline tumors and 40 of apparently healthy ovarian sections which were included as baseline control .The mean age of the patients with ovarian carcinoma was higher (42.58±8.083years) than the mean age of the borderline ovarian tumor (41.90±10.126 ) and benign tumors group (39.82± 7.646 years), followed by mean age of those females in the group of apparently healthy control  (35.64± 10.183). The results of immunohistochemistry staining of LMP1-EBV gene expression  showed that  57.8% ( 26 out of 45 tissues) was positive in malignant ovarian tumors .While, in benign ovarian tumors the positive results was 40 % (18 out of 45 tissues) of LMP1-EBV. Whereas, the positive results in borderline ovarian tumor group was 40% (8 out of 20 tissues), followed by the apparently healthy ovarian control tissues was 15% (6 out of 40 tissues).